The History of Turkish Labour Relations as a Figuration: An Eliasian Reading - Man, Fuat (Italian Sociological Review, 2026)
The history of labour relations in Turkey has predominantly been examined through a simplistic chronological framework, with studies grounded in comprehensive theoretical foundations being exceedingly rare. This study offers a reinterpretation of Turkey’s labour relations history by employing the concept of “figuration” developed by Norbert Elias, a prominent figure in contemporary social theory. It focuses on three key historical moments: the period of the first labour law’s enactment, the post-World War II era, and the early 2000s. The analysis aims to illustrate how labour relations have been shaped by complex and dynamic interactions rather than the absolute power of any single actor. Drawing on Elias’s game models as an analytical framework, the study argues that labour relations resemble a game, where each actor’s actions influence and are influenced by others. Empirical data from the three historical moments are utilized to substantiate this perspective, providing a fresh theoretical approach to understanding Turkey’s labour relations history.